Thyroid hormones and vitamin D in patients with breast cancer with mutations in BRCA1 or BRCA2 genes - Kolben, Thomas; Toth, Bettina (Anticancer research, 2016)
Aim: The thyroid hormones free triiodothyronine (fT3), free thyroxine (fT4), thyroid-stimulating hormone (TSH) and vitamin D seem to be involved in the process of differentiation and proliferation of breast tissue. Little is known about these factors in breast cancer 1 and 2 (BRCA1/BRCA2)-mutation carriers with breast cancer (BC). The purpose of this investigation was to evaluate the association of thyroid gland function and vitamin D with BC in patients with BRCA mutations. Patients and Methods: At the Department of Hereditary Breast and Ovarian Cancer of the Ludwig Maximilian University Hospital of Munich, 40 patients with BC (10 patients with mutations in the BRCA1 gene, 10 with mutations in the BRCA2 gene, and 20 without mutations, as control group) were selected for analysis of the following parameters: fT3, fT4, TSH and vitamin D. The primary diagnosis was made between 21 and 62 years of age. The patients were matched by age. Anamnestic data were evaluated concerning disorders of the thyroid gland and primary BC diagnosis. Results: In patients with BC, BRCA mutations are not associated with thyroidal dysfunctions. A significantly increased level of vitamin D in BRCA2-mutation carriers compared to those without mutation (p=0.02) was detected. The grade of the tumors in the BRCA2 group was better than in those with mutation. BRCA1-mutation carriers had an increased incidence of primary BC diagnosis during pregnancy (30% vs. 0%) in comparison to those without mutation. Conclusion: No association between the thyroid hormones and BC in BRCA1/2-mutation carriers was found. Vitamin D was significantly elevated in BRCA2-mutation carriers and the observation of a better tumor grade in this group could be consistent with the ability of vitamin D to inhibit growth and induce differentiation.
Gesehen am 12.08.2019